PP.LB01.21: A PROPOSAL FOR THE IDEA OF A FLEXIBLE-COMBINATION POLYPILL IN ARTERIAL HYPERTENSION. (June 2015) - Fommei, E.; Ghione, S.; Biagini, S.; Corrao, G.; Mancia, G.
Abstract : Objective: Modern pharmaceutical strategies in arterial hypertension, as well as in other fields, are directed toward two major apparently contrasting objectives: 1) simplification of treatment by grouping multiple drugs into single fixed-combination pharmaceutical units (including "polypill") to improve patient adherence, and 2: personalization of therapy to tailor treatments according to specific individual aspects including pharmacogenomics. The combined fulfillment of these objectives would conceivably entail the unrealistic development of a very great variety of fixed-combination polypills, each different for drug composition and dosage. An alternative view that could combine the need for both therapy simplification and personalization may be the concept of a flexible-combination polypill. Design and Methods: In order to test this approach, we are devising a preliminary study aimed to assess the feasibility and efficacy of shifting individual patients' treatment from multiple daily administration (multi-administration) to a single once-a-day administration (mono-administration) of the same drugs. After approval of Ethical Committee, a cross-over randomized study will be carried out for 24 weeks in 52 well controlled non complicated hypertensive outpatients under multiple therapy with at least one hypotensive drug and/or a statin and/or aspirin. Each subject will remain for an 8 weeks period on multi-administration and for another 8 weeks period on mono-administration of the same therapy; the two periods will be separated by 8 weeks to avoid a carry-over effect and their sequence will be randomized. Results: The study will provide information on the effects of mono-administration in comparison with multi-administration of the same drugs on adherence to treatment, adverse events, ambulatory blood pressure monitoring and lipid profile. Conclusions: If results will be favorable, they could prompt large scale studies following the idea of a flexible-combination polypill and addressing the various regulatory and technological issues in the path for its realization and production systems.